Traditional Herbal Management of Sickle Cell Anemia: Lessons from Nigeria. (8th November 2012) - Ameh, Sunday J.; Tarfa, Florence D.; Ebeshi, Benjamin U.
Abstract : Background . Patients in West Africa where sickle cell anemia (SCA) is endemic have for ages been treated with natural products, especially herbs, as, is still the case in rural communities. Objective . In this paper we look closely at some of these herbs to see if there are any lessons to be learnt or clues to be found for optimizing the treatments based on them, as had been done in the case of NIPRISAN, which was developed from herbs in Nigeria based on Yoruba Medicine. Methods . Select publications on SCA, its molecular biology and pathology, and actual and experimental cases of herbal treatment were perused in search of molecular clues that can be linked to chemical constituents of the herbs involved. Results . The study revealed that during the last 2-3 decades, much progress was made in several aspects of SCA pharmacology, especially the approval of hydroxyurea. As for SCA herbalism, this paper revealed that antisickling herbs abound in West Africa and that the most promising may yet be found. Three new antisickling herbs ( Entandrophragma utile, Chenopodium ambrosioides, and Petiveria alliacea ) were reported in May 2011. At NIPRD, where NIPRISAN was developed, three other recipes are currently awaiting development. Conclusion . The study raised the hope that the search in the Tropics for more effective herbal recipes for managing sickle cell anaemia will be more fruitful with time and effort.